On the welfare analysis of external reference pricing and reimbursement policy - Dong, Van-Chung; Lin, Yan-Shu; Shih, Pei-Cyuan (Estudios de Economía, 2023)
The co-existence of external referencing pricing (ERP) and reimbursement policy is common in many countries. Thus, this research examines whether or not the imposition of ERP is socially desirable in the presence of reimbursement policy. For direct sales channel, we find that the home social welfare is worse-off with ERP if the home copayment rate is too high. Our main results are robust under indirect sales channel. Moreover, the home social welfare under the pharmacypurchasing-price (PPP) ERP is larger than that under the ex-factory-price (EFP) ERP if the home copayment rate is high enough. Finally, the profit of brand-name firm under indirect sales channel is higher than that under direct sales channel if the home copayment rate is too high.